Acoustic evidence for topographic blocking on a steep submarine canyon wall - Astrid B. Leitner; Chad M. Waluk; Kim R. Reisenbichler; Rob E. Sherlock; Bruce H. Robison; Kelly J. Benoit‐Bird (Limnology and Oceanography, 2026)
Diel vertical migration (DVM) is the largest mass‐movement of animals on Earth, with profound ecological and biogeochemical consequences. DVM has mostly been studied in the open ocean; however, at steep slopes, pelagic animals including vertical migrators must contend with the seafloor, emphasizing the importance of understanding DVM in these prevalent, critical habitats. Here we used active acoustics in combination with video to conduct a detailed study of the interactions of vertical migrators with the steep wall of a submarine canyon during their sunrise descent. We found regular and frequent, high‐density sunrise aggregations of animals consistent with seafloor blocking of descending vertical migrators across all seasons. While topographic blocking was thought to be primarily caused by nighttime advection of migrators over shallows by prevailing currents, here the occurrence of this phenomenon was observed to be largely independent of oceanographic drivers including advection as measured by an ADCP, providing evidence that behavior plays an important role. Advection, season, upwelling, and other environmental factors were found to impact specific characteristics of sunrise aggregations but not likelihood of occurrence. Given its intensity and prevalence, topographic blocking likely creates high‐quality, predictable foraging opportunities for a large diversity of predators and influences the abundance and habitat use of predators in the area. The steep slopes of this canyon, as with any abrupt bathymetry, juxtapose the deep and the shallow, the benthic and the pelagic, and the offshore and nearshore. Thus, topographic blocking may be prevalent in other steep canyons and at steep bathymetry more generally.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Discovery and description of a remarkable bathypelagic nudibranch, Bathydevius caudactylus, gen. et. sp. nov. - Bruce H. Robison; Steven H.D. Haddock (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Giant eggs in a deep‐sea squid - Henk‐Jan T. Hoving; Steven H. D. Haddock; Bruce H. Robison; Brad A. Seibel (Ecology, 2024)

Running the Gauntlet: Assessing the Threats to Vertical Migrators - Bruce H. Robison; Rob E. Sherlock; Kim R. Reisenbichler; Paul R. McGill (Frontiers in Marine Science, 2020)

“Little Red Jellies” in Monterey Bay, California (Cnidaria: Hydrozoa: Trachymedusae: Rhopalonematidae) - George I. Matsumoto; Bastian Bentlage; Rob Sherlock; Kristine Walz; Bruce H. Robison (Frontiers in Marine Science, 2020)

Particulate matter flux interception in oceanic mesoscale eddies by the polychaete Poeobius sp. - Svenja Christiansen; Henk‐Jan Hoving; Florian Schütte; Helena Hauss; Johannes Karstensen; Arne Körtzinger; Simon‐Martin Schröder; Lars Stemmann; Bernd Christiansen; Marc Picheral; Peter Brandt; Bruce Robison; et al. (Limnology and Oceanography, 2018)
Gelatinous zooplankton hold key functions in the ocean and have been shown to significantly influence the transport of organic carbon to the deep sea. We discovered a gelatinous, flux‐feeding polychaete of the genus Poeobius in very high abundances in a mesoscale eddy in the tropical Atlantic Ocean, where it co‐occurred with extremely low particle concentrations. Subsequent analysis of an extensive in situ imaging dataset revealed that Poeobius sp. occurred sporadically between 5°S–20°N and 16°W–46°W in the upper 1000 m. Abundances were significantly elevated and the depth distribution compressed in anticyclonic modewater eddies (ACMEs). In two ACMEs, high Poeobius sp. abundances were associated with strongly reduced particle concentrations and fluxes in the layers directly below the polychaete. We discuss possible reasons for the elevated abundances of Poeobius sp. in ACMEs and provide estimations showing that a single zooplankton species can completely intercept the downward particle flux by feeding with their mucous nets, thereby substantially altering the biogeochemical setting within the eddy.

The Coevolution of Midwater Research and ROV Technology at MBARI - Bruce Robison; Kim Reisenbichler; Rob Sherlock (Oceanography, 2017)

BOOK REVIEW • A Sea of Glass: Searching for the Blaschkas’ Fragile Legacy in an Ocean at Risk - Bruce Robison (Oceanography, 2017)

Islands of Ice: Influence of Free-Drifting Antarctic Icebergs on Pelagic Marine Ecosystems - Maria Vernet; Kenneth Smith; Adrián Cefarelli; John Helly; Ronald Kaufmann; Hai Lin; David Long; Alison Murray; Bruce Robison; Henry Ruhl; Timothy Shaw; Alana Sherman; et al. (Oceanography, 2012)

Seasonality and depth distribution of a mesopelagic foraminifer, Hastigerinella digitata , in Monterey Bay, California - Pincelli M. Hull; Karen J. Osborn; Richard D. Norris; Bruce H. Robison (Limnology and Oceanography, 2011)
We investigated the habitat depth and population dynamics of mesopelagic foraminifera in Monterey Bay, California, using 12 yr of video surveys and specimens from live collections. The water column over Monterey Canyon continuously supports two distinct species of mesopelagic foraminifera, Hastigerinella digitata and a previously unknown species referred to as Hastigerina sp., with H. digitata dominating the planktonic foraminiferal assemblage at mesopelagic depths. H. digitata populations live within a narrow depth horizon that lies above the core of the regional oxygen minimum zone at a depth of 280–358 m and O 2 concentrations of 1–1.3 mL L −1 . Our observations provide a modern calibration for understanding fossil digitate planktonic foraminifera. We observed numerous copepods in various stages of ingestion on the spines of H. digitata and a conspicuous lack of detritus attached to the spine network, providing support for the hypothesis that H. digitata is an obligate carnivore. H. digitata populations did not show the strong two‐phase seasonality that characterizes the population dynamics of many mesopelagic species that live above the Monterey Canyon, although H. digitata was generally more abundant in cooler waters on seasonal and interannual timescales.

Conservation of Deep Pelagic Biodiversity - BRUCE H. ROBISON (Conservation Biology, 2009)
The deep ocean is home to the largest ecosystems on our planet. This vast realm contains what may be the greatest number of animal species, the greatest biomass, and the greatest number of individual organisms in the living world. Humans have explored the deep ocean for about 150 years, and most of what is known is based on studies of the deep seafloor. In contrast, the water column above the deep seabed comprises more than 90% of the living space, yet less than 1% of this biome has been explored. The deep pelagic biota is the largest and least‐known major faunal group on Earth despite its obvious importance at the global scale. Pelagic species represent an incomparable reservoir of biodiversity. Although we have yet to discover and describe the majority of these species, the threats to their continued existence are numerous and growing. Conserving deep pelagic biodiversity is a problem of global proportions that has never been addressed comprehensively. The potential effects of these threats include the extensive restructuring of entire ecosystems, changes in the geographical ranges of many species, large‐scale elimination of taxa, and a decline in biodiversity at all scales. This review provides an initial framework of threat assessment for confronting the challenge of conserving deep pelagic biodiversity; and it outlines the need for baseline surveys and protected areas as preliminary policy goals.

Feeding behavior of the ctenophore Thalassocalyce inconstans: revision of anatomy of the order Thalassocalycida - Holly F. Swift; William M. Hamner; Bruce H. Robison; Laurence P. Madin (Marine Biology, 2009)

Ink utilization by mesopelagic squid - Stephanie L. Bush; Bruce H. Robison (Marine Biology, 2007)

A comparison of absorption and assimilation efficiencies between four species of shallow- and deep-living fishes - Jeffrey C. Drazen; Kim R. Reisenbichler; Bruce H. Robison (Marine Biology, 2007)

Chemically regulated feeding by a midwater medusa - Mario N. Tamburri; Magdalena N. Halt; Bruce H. Robison (Limnology and Oceanography, 2000)
Planktonic cnidarians are principal predators in the vast habitats between the ocean's surface and the deep‐sea floor. Almost nothing is known, however, about the chemical ecology of these fragile midwater animals because of difficulties associated with collecting healthy specimens and con‐ducting experiments in the field. With the use of a remotely operated vehicle, we found that the hydromedusa Mitrocoma cellularia is not a passive “drift‐net” predator. This relatively simple gelatinous organism reacted to both the taste and smell of prey in the laboratory and in situ. Our results comprise the first definitive demonstration that a species of pelagic cnidarian responds behaviorally to chemical signals, and they lend new insight into the role of chemoreception in structuring mid‐water communities.